The Development of Essay Writing Skills Through Multimedia for Mathayom Suksa 4 Students at Praphassorn Wittaya School, Khon Kaen Province - Naruttamo (Laophakdee), Noppakao; Phrakrukhamphithammanuwat; Sribunrueang, Pacharakit (Journal of Buddhist Education and Research (JBER), 2026)
This study aimed to: (1) develop a multimedia-based learning management plan for essay writing that meets the 80/80 efficiency criterion, (2) compare students’ essay writing achievement before and after the implementation of multimedia instruction, and (3) examine students’ satisfaction toward the instructional approach. The participants consisted of 22 Grade 10 students at Praphatsorn Witthaya School, Khon Kaen Province, Thailand. The research instruments included multimedia-based lesson plans, an essay writing achievement test, and a student satisfaction questionnaire. Data were analyzed using mean, standard deviation, and dependent samples t-test. The research results were as follows: (1) the developed learning management plan achieved an efficiency level of 25.45/84.85, exceeding the established 80/80 criterion; (2) students’ post-test scores were significantly higher than their pre-test scores at the .05 level; and (3) overall student satisfaction was at the highest level (M = 4.43). The results indicate that multimedia-integrated instruction effectively enhances students’ essay writing skills and promotes positive learning engagement. The study suggests that multimedia learning environments can serve as an effective pedagogical approach for developing writing competence in Thai language education in the digital era.